Response to Pralsetinib Observed in Meningeal-Metastatic EGFR-Mutant NSCLC With Acquired RET Fusion: A Brief Report - Zichen Zhao, MD; Chao Su, PhD; Weigang Xiu, MD; Weiya Wang, MD; Shasha Zeng, MD; Meijuan Huang, MD; Youling Gong, MD; You Lu, MD, PhD; Yan Zhang, MD, PhD (JTO Clinical and Research Reports, 2022)
Introduction: RET is well known as an important driver gene in NSCLC. Moreover, RET is a rare acquired resistance mechanism to EGFR-mutant NSCLC. Only 36 NSCLC cases of coexistence of EGFR and RET were reported previously worldwide. So far, there have been no reports on the following: (1) whether combination of EGFR tyrosine kinase inhibitor (TKI) and RET TKI works for meningeal metastasis; (2) the concentrations of EGFR TKI and RET TKI in the cerebrospinal fluid (CSF) and plasma; and (3) whether RET fusions and EGFR mutation happened in the same clone or not. Methods: We reported a patient with an EGFR-mutant NSCLC with acquired RET fusions and meningeal metastasis treated with pralsetinib and osimertinib; the specimen was analyzed by next-generation sequencing (Illumina NovaSeq 6000 platform). Symptom improvement and magnetic resonance imaging scan were used for effect evaluation. Furthermore, we determined the concentrations of pralsetinib and osimertinib in CSF and plasma by means of liquid chromatography tandem mass spectrometry. We also detected RET fusion and EGFR L858R mutation by methods of fluorescence in situ hybridization and immunohistochemistry with continuous sections to analyze whether RET fusions coexist with EGFR mutation in the same clone or not. Results: The allele frequency of the RET fusion was detected to be 12.88%. This patient achieved a partial response, indicating pralsetinib combined with osimertinib may be clinically beneficial for meningeal metastasis in patients harboring acquired coexistent RET fusions. The concentrations of pralsetinib in the CSF and plasma were 704.76 nM and 91.31 μM, whereas those of osimertinib in the CSF and plasma were 23.70 nM and 2148.94 nM, respectively. RET fusion was found in the same clone of EGFR L858R mutation. Conclusions: Our finding of this case indicated that RET fusion and EGFR mutation occur in the same population of cell clones, rather than in different cell clones. Combined pralsetinib may be an effective way to overcome the resistance, even for meningeal metastasis, owing to high CSF distribution of pralsetinib.